2015
DOI: 10.24329/aspikom.v2i4.78
|View full text |Cite
|
Sign up to set email alerts
|

Audit Komunikasi Organisasi Wahana Lingkungan Hidup Indonesia (Walhi) Yogyakarta

Abstract: Keywords : Communication Audit, Horizontal-Vertical Communication, Communication Media AbstrakPenelitian ini bertujuan menganalisis proses pelaksanaan audit komunikasi organisasi pada Organisasi WALHI Yogyakarta terhadap peningkatan sistem organisasi untuk meningkatkan efektivitas organisasi. Penelitian ini menggunakan teori informasi organisasi dan metode deskriptif kualitatif. Temuan penelitian ini menggambarkan proses pelaksanaan audit komunikasi organisasi WALHI Yogyakarta sudah berjalan cukup baik. Hal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Supra Matra Abadi PMKS Aek Nabara. In this study, researchers conducted participatory observations by collecting research data through observation and sensing where researchers were involved in the daily lives of informants (Ramadani et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Supra Matra Abadi PMKS Aek Nabara. In this study, researchers conducted participatory observations by collecting research data through observation and sensing where researchers were involved in the daily lives of informants (Ramadani et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…A comfortable and safe physical environment can help employees to focus on their work and minimize distractions, leading to increased productivity. A study conducted in Nigeria found that there was a statistically significant correlation between the physical environment/ergonomics of the workplace and productivity of small-scale enterprises (Ramadani et al, 2015).…”
Section: Effect Of Work Environment (X3) On Employee Productivity (Y)mentioning
confidence: 99%
“…Myron Emmanual (Ramadani et al, 2015) argues that, generally, a communication audit is a complete study of a company's structure, flow, and practices of communication. The South Botn Bawaslu has executed its job in communicating and directing the performance of each division and staff member.…”
Section: Input Stage Evaluationmentioning
confidence: 99%